Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the equation step by step.
Given the equation:
[tex]\[ (\cos 3\theta)(\cos \theta) + 1 = (\sin 3\theta)(\sin \theta) \][/tex]
We can start by using trigonometric identities. Recall the product-to-sum identities:
[tex]\[ \cos A \cos B = \frac{1}{2} [\cos (A + B) + \cos (A - B)] \][/tex]
and
[tex]\[ \sin A \sin B = \frac{1}{2} [\cos (A - B) - \cos (A + B)] \][/tex]
Using [tex]\(A = 3\theta\)[/tex] and [tex]\(B = \theta\)[/tex], we have:
[tex]\[ \cos 3\theta \cos \theta = \frac{1}{2} [\cos (3\theta + \theta) + \cos (3\theta - \theta)] = \frac{1}{2} [\cos 4\theta + \cos 2\theta] \][/tex]
and
[tex]\[ \sin 3\theta \sin \theta = \frac{1}{2} [\cos (3\theta - \theta) - \cos (3\theta + \theta)] = \frac{1}{2} [\cos 2\theta - \cos 4\theta] \][/tex]
Substitute these into the given equation:
[tex]\[ \frac{1}{2} [\cos 4\theta + \cos 2\theta] + 1 = \frac{1}{2} [\cos 2\theta - \cos 4\theta] \][/tex]
Multiply through by 2 to clear the fractions:
[tex]\[ \cos 4\theta + \cos 2\theta + 2 = \cos 2\theta - \cos 4\theta \][/tex]
Rearrange terms to combine like terms:
[tex]\[ \cos 4\theta + \cos 2\theta + 2 = \cos 2\theta - \cos 4\theta \][/tex]
Combine the [tex]\(\cos 4\theta\)[/tex] terms:
[tex]\[ 2\cos 4\theta + 2 = 0 \][/tex]
Subtract 2 from both sides:
[tex]\[ 2\cos 4\theta = -2 \][/tex]
Divide by 2:
[tex]\[ \cos 4\theta = -1 \][/tex]
The general solution to [tex]\(\cos (x) = -1\)[/tex] is:
[tex]\[ x = \pi + 2k\pi \quad \text{for integer } k \][/tex]
Set [tex]\(x = 4\theta\)[/tex]:
[tex]\[ 4\theta = \pi + 2k\pi \][/tex]
Solve for [tex]\(\theta\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} + \frac{k\pi}{2} \][/tex]
Now, let's find the specific values of [tex]\(\theta\)[/tex] that satisfy the original equation within one full cycle (0 to [tex]\(2\pi\)[/tex]). We consider the first few values of [tex]\(k\)[/tex]:
For [tex]\(k = 0\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} \][/tex]
For [tex]\(k = 1\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} + \frac{\pi}{2} = \frac{3\pi}{4} \][/tex]
For [tex]\(k = -1\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} - \frac{\pi}{2} = -\frac{\pi}{4} \][/tex]
For [tex]\(k = -2\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} - \pi = -\frac{3\pi}{4} \][/tex]
Thus, the solutions to the equation [tex]\((\cos 3\theta)(\cos \theta) + 1 = (\sin 3\theta)(\sin \theta) \)[/tex] are:
[tex]\[ \theta = -\frac{3\pi}{4}, -\frac{\pi}{4}, \frac{\pi}{4}, \frac{3\pi}{4} \][/tex]
Given the equation:
[tex]\[ (\cos 3\theta)(\cos \theta) + 1 = (\sin 3\theta)(\sin \theta) \][/tex]
We can start by using trigonometric identities. Recall the product-to-sum identities:
[tex]\[ \cos A \cos B = \frac{1}{2} [\cos (A + B) + \cos (A - B)] \][/tex]
and
[tex]\[ \sin A \sin B = \frac{1}{2} [\cos (A - B) - \cos (A + B)] \][/tex]
Using [tex]\(A = 3\theta\)[/tex] and [tex]\(B = \theta\)[/tex], we have:
[tex]\[ \cos 3\theta \cos \theta = \frac{1}{2} [\cos (3\theta + \theta) + \cos (3\theta - \theta)] = \frac{1}{2} [\cos 4\theta + \cos 2\theta] \][/tex]
and
[tex]\[ \sin 3\theta \sin \theta = \frac{1}{2} [\cos (3\theta - \theta) - \cos (3\theta + \theta)] = \frac{1}{2} [\cos 2\theta - \cos 4\theta] \][/tex]
Substitute these into the given equation:
[tex]\[ \frac{1}{2} [\cos 4\theta + \cos 2\theta] + 1 = \frac{1}{2} [\cos 2\theta - \cos 4\theta] \][/tex]
Multiply through by 2 to clear the fractions:
[tex]\[ \cos 4\theta + \cos 2\theta + 2 = \cos 2\theta - \cos 4\theta \][/tex]
Rearrange terms to combine like terms:
[tex]\[ \cos 4\theta + \cos 2\theta + 2 = \cos 2\theta - \cos 4\theta \][/tex]
Combine the [tex]\(\cos 4\theta\)[/tex] terms:
[tex]\[ 2\cos 4\theta + 2 = 0 \][/tex]
Subtract 2 from both sides:
[tex]\[ 2\cos 4\theta = -2 \][/tex]
Divide by 2:
[tex]\[ \cos 4\theta = -1 \][/tex]
The general solution to [tex]\(\cos (x) = -1\)[/tex] is:
[tex]\[ x = \pi + 2k\pi \quad \text{for integer } k \][/tex]
Set [tex]\(x = 4\theta\)[/tex]:
[tex]\[ 4\theta = \pi + 2k\pi \][/tex]
Solve for [tex]\(\theta\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} + \frac{k\pi}{2} \][/tex]
Now, let's find the specific values of [tex]\(\theta\)[/tex] that satisfy the original equation within one full cycle (0 to [tex]\(2\pi\)[/tex]). We consider the first few values of [tex]\(k\)[/tex]:
For [tex]\(k = 0\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} \][/tex]
For [tex]\(k = 1\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} + \frac{\pi}{2} = \frac{3\pi}{4} \][/tex]
For [tex]\(k = -1\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} - \frac{\pi}{2} = -\frac{\pi}{4} \][/tex]
For [tex]\(k = -2\)[/tex]:
[tex]\[ \theta = \frac{\pi}{4} - \pi = -\frac{3\pi}{4} \][/tex]
Thus, the solutions to the equation [tex]\((\cos 3\theta)(\cos \theta) + 1 = (\sin 3\theta)(\sin \theta) \)[/tex] are:
[tex]\[ \theta = -\frac{3\pi}{4}, -\frac{\pi}{4}, \frac{\pi}{4}, \frac{3\pi}{4} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.